MODEL BANGKITAN PERGERAKAN RUMAH TANGGA BERDASARKAN GENDER UNTUK AKTIFITAS MANDOTORY DI KOTA BANDA ACEH - Raihan Icthiar Riyana; Renni Anggraini; Sugiarto Sugiarto (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Trip generation in the household is very influential on the activity it has. Routine activity that should be done by an individual itself also called as mandatory activity. Also with the trip generation performed can be affected by social status owned, one of which is gender. Gender is the division of roles between men and women which can have a difference. The occurrence of traffic density due to the characteristics of community within a household of trip generation making the purpose of this research is to know the socio-economic characteristics, demography and tip behavior, knowing factors which influence the trip generation of a household based on gender for mandatory activity and to get the model, and the difference of utility and probability value. Area of this research are 4 sub-districts in Banda Aceh city which are Jaya Baru sub-districts, Banda raya, Lueng Bata, and Kuta raja sub-district with the sampe numbers of 400 samples. Method used is Model of Binomial Logit Difference then processed by using SPSS v20. Characteristics of Socio-economic, demography, and trip behavior which produced by 19 variables in this research one of its variable is gender that is 54% for men and 46% for women. From the utility model obtained, then the factors that affecting the movement of the household based on mandatory activity on men are number of family members and activity duration, while for women are number of family members who attend school and activity duration. Probability for the household Trip generation is probabilitas ≤ 3 movement and greater than 3 movements based on the mandatory activity for men are 75% and 25%, while for women are 72% and 28%.